Effect of Chilling Imbibition on Seed Germination - Abbas, M. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
Tomato (Lycopersicon esculentum Mill) and cucumber (Cucumis sativus L.) seeds were imbided with water at 10°c or 4°c for 4, 8, and 16 hours before planting to study germination rate, mean germination time, and final germination percentage as well as electrolyte leakage from chilled seeds. Seeds imbided more water at 10°c compared to that at 4°c. Coefficient velocity of germination and final percent of germination decreased with the decrease of temperature and increasing time of imbibition. Germination percent under laboratory conditions was higher than that under field conditions. Also, it was found that tomato seeds were more sensitive to chilling imbibition. Electrolyte leakage increased as temperature of imbibition increases.